Curses and Rituals as Antidotes: The Significance of Offerings in Dreadlocks Cutting Ritual for Santri - Muhamad Agus Mushodiq; Wahyudi Wahyudi; Ahmad Muslimin; Dedi Setiawan; M. Sayyidul Abrori; Saidun Anwar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The deadlocks cutting ritual, known as ‘ruwatan rambut gimbal’ is one of the events in the Dieng Culture Festival which requires the presence of uborampe in its implementation. This study aims to reveal the symbolic significance of the uborampe which share a conceptual similarity with totems. This study uses a qualitative research with a semiotics analysis of Charles Sanders Peirce. The findings of this research indicate that: first, the uborempe presented in the ritual can be called a totem because it comes from animals and plants and symbolizes other sacred things. Second, the people of Dieng Banjarnegara are adherents of limited totemism or quasi totemism, because the totem in the dreadlock cutting ritual is not worshiped but contains an element of expected prayer. Third, forms of syncretism between Hindu, Javanese, and Islam appear in the use of prayer in Javanese and their meaning and offering of uborampe ritual. Fourth, the meaning of the totem in the treatment of the dreadlock cutting ritual in the perspective of Charles Sanders Peirce's Semiotics is categorised in three forms: symbols, icons, and cum icon symbols. The symbolic significance of one uborempe can be manifested in various meanings adjusted to the community that carries out the interpretation.